2014
DOI: 10.1016/j.ttbdis.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of protective behaviour against ticks in the UK: A mixed methods study

Abstract: The objective of this research was to determine the most appropriate protective behaviours to promote in order to protect members of the public from Lyme borreliosis, to identify the drivers and barriers for these behaviours, and to determine the strongest predictors of tick-protective behaviour. We used a mixed methods study with qualitative interviews and a quantitative web survey. Interviews with topic experts and members of the public suggested that predictors of tick checking included perceived disease li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 21 publications
5
37
0
Order By: Relevance
“…In Phillips and colleagues [28], women were also associated with a greater proportion of preventive behaviors including the practice of risk area avoidance, tick checks and tick repellent in residents of Nantucket Island in Massachusetts, United States. On the opposite, other studies have found no gender differences regarding LD preventive behaviors adoption [30,34]. …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In Phillips and colleagues [28], women were also associated with a greater proportion of preventive behaviors including the practice of risk area avoidance, tick checks and tick repellent in residents of Nantucket Island in Massachusetts, United States. On the opposite, other studies have found no gender differences regarding LD preventive behaviors adoption [30,34]. …”
Section: Discussionmentioning
confidence: 81%
“…Our findings may also suggest that despite their demonstrated efficacy, some preventive measures, such as applying acaricides on one’s property, are not popular in either Quebec or Switzerland, a finding which may also be explained by the low level of social acceptability for this specific measure. Previous studies have shown a low level of adoption for similar preventive measures both in low and high incidence regions for LD in other parts of the world [20,28,30,34,40]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Usually, a tick check would be done after leaving a risk area, although it also is prudent to check for ticks that might be moving over clothing or skin while in tick habitats, although this would seem to be rarely done by exposed persons. 51 Removal of attached ticks is ideally done with fine-tipped, stiff, and angled forceps (tweezers) placed around the head of the tick as near as is possible to the skin, followed by a steady, upward pulling movement [52][53][54][55] (Fig. 1).…”
Section: Tick Checksmentioning
confidence: 99%
“…Whilst some innovations promise greater risk reduction, especially those relating to acaracide treated clothes [33], basic social barriers to engagement remain. For instance, in recent work by Mowbray et al [34] respondents stated they would not follow advice to tuck trousers into socks. A common explanation for why: 'Because I'd look stupid' .…”
Section: Introductionmentioning
confidence: 99%